Faktor Penyebab Kekambuhan pada Mantan Penyalahguna NAPZA - Wahyu Dini Candra Susila; Novy Helena Catharina Daulima (FORIKES, 2020)
Misuse of Narcotics, Psychotropic and Other Addictive Substances is still a problem in the community. International drug abuse has increased. Drug dependence can be rehabilitated medically but rehabilitation does not guarantee that a drug addict will recover from his addiction. Many users, even though they have undergone rehabilitation programs, have not been able to truly leave drug or recover. The purpose of this paper is to find out in detail the factors that influence the relapse behavior of former drug users. The writing method used in this article was a literature review, which searched in 5 international databases were Science Direct, Willey Online Library, Sage Journal, and ProQuest. The author used several search keywords namely